Natural Resource-Based Food Supply Chain in Development of the Masela Block - Maryam Sangadji; Muspida; Lussi R Loppies (Cita Konsultindo Research Center, 2022)
This study aims to examine the supply chain for food needs based on the natural resources of the Tanimbar Islands in the face of Masela Block development The availability of components for distributors, cooperatives / Village-Owned Enterprises (BUMDES), farmer producers, home industries, inter-island traders, supermarkets/markets / retail and the Regional Investment Coordinating Board (BKPMD) has not yet become the main component of the supply chain system for meeting food needs principal The study was conducted with a qualitative approach, using a sample area of sub-districts and villages by